Dissecting hiPSC-CM pacemaker function in a cardiac organoid model. (June 2019) - Schulze, Mirja L.; Lemoine, Marc D.; Fischer, Alexander W.; Scherschel, Katharina; David, Robert; Riecken, Kristoffer; Hansen, Arne; Eschenhagen, Thomas; Ulmer, Bärbel M.
Abstract: Biological pacemakers could be a promising alternative to electronic pacemakers and human induced pluripotent stem cell derived cardiomyocytes (hiPSC-CM) may represent a suitable source for implantable cells. To further unravel this potential a thorough understanding of pacemaker function with regard to coupling processes both in the physiological and in the graft-host context is required. Here we developed a 2-component cardiac organoid model with a hiPSC-CM embryoid body (EB) as trigger casted into a rat engineered heart tissue (EHT) as arrhythmic beating substrate. Contractility recordings revealed that the EB controlled the beating activity of the EHT, leading to a regular hiPSC-CM-like beating pattern instead of the irregular beating typically seen in rat EHT. Connectivity was observed with action potential (AP) measurements and calcium transients transmitting from the EB directly into the rat EHT. Immunohistochemistry and genetically labeled hiPSC-CMs demonstrated that EB-derived and rat cells intermingled and formed a transitional zone. Connexin 43 expression followed the same pattern as histological and computer models have indicated for the human sinoatrial node. In conclusion, hiPSC-CM EBs function as a biological pacemaker in a 2-component cardiac organoid model, which provides the possibility to study electrophysiological and structural coupling mechanisms underlying propagation of pacemaker activity.